Brown Coconut Husks as Media Within an Anaerobic Filter for Improving On-Site Wastewater Treatment - Nicola Brown; John Edwards; Shogo Yarita; Sylvia Chia (Applied Sciences)
Many small communities rely on on-site wastewater treatment systems such as septic tanks; however, there are concerns regarding the level of wastewater treatment being achieved. Appropriate solutions for these communities are needed to upgrade existing septic tanks. Anaerobic filters are a potential solution, which can be added downstream of the septic tank and operate by containing media which allow a biofilm to form. Ideally, this media would be easily accessible and affordable. In this work, the use of brown coconut husks is investigated, and it is found that 68% of the chemical oxygen demand (COD) can be removed by these systems. Nutrient levels were also monitored in the effluent to determine whether the leaching of nutrients from the coconut husks is a concern. It was found that initially some nitrogen and phosphorus had leached but these were washed out of the reactor very quickly and had a minimal impact on the effluent concentrations. Examination of the coconut husks after 10 months of operation showed no signs of the coconut husks beginning to break down, suggesting that the use of coconut husks as media in anaerobic filters should be investigated further.